The ammonia absorption spectrum between 3900 and 4700 cm−1. (January 2022) - Cacciani, P.; Čermák, P.; Vander Auwera, J.; Campargue, A.
Highlights: Room temperature Fourier transform absorption spectra of ammonia were recorded at four pressures in the 2.3 µm atmospheric window. 7794 15 NH3 and 625 15 NH3 transitions were identified in the 3900 - 4706 cm−1 region. The theoretical spectra available in the literature and lower state combination difference relations were used to assign the 14 NH3 lines. For 14 NH3, 6052 transitions were assigned to 51 vibrational bands providing 2287 experimental energy levels with 1870 new ones. The assigned transitions representing over 99.8% of room temperature 14 NH3 integrated absorption in the region will be valuable to improve spectroscopic databases. Abstract: Room temperature absorption spectra of ammonia have been recorded by high-resolution Fourier transform spectroscopy in the range 3900-4700 cm –1 at four pressures (13, 46, 140, and 304 Pa). The investigated spectral region overlaps the important 2.3 µm atmospheric transparency window. 8419 absorption lines were retrieved from the recorded spectra. Line intensities range between 1 × 10 −25 and 1.6 × 10 −20 cm/molecule. The rovibrational assignments, relying on the position and intensity agreement with the C2018 theoretical line list (Coles et al. 2018), were validated by the systematic use of Lower State Combination Difference (LSCD) relations. 6052 transitions were assigned to 51 vibrational bands of the main isotopologue, 14 NH3, and 625 transitions of the 15 NH3 minor isotopologue were identified. Overall, the assigned transitions represent over 99.8% of the integrated absorption at room temperature in the region. The upper state empirical energy of a total of 2287 rovibrational levels of 14 NH3 were derived. Among them, 1870 are newly reported. The achieved quality of the LSCD relations indicates that the accuracy of the derived energy levels is better than 0.001 cm −1 . Comparison with the HITRAN2020 list shows that the present results will be valuable in improving the ammonia spectroscopic databases in the region, both in terms of completeness and accuracy of the line positions and line intensities. A recommended line list for ammonia in natural isotopic abundance is provided for the studied region. Graphical abstract: Image, graphical abstract